41. ∫sinhxdx
∫sinhxdx=∫2ex−e−xdx=21(∫exdx−∫e−xdx)=2ex+e−x=coshx+C
42. ∫sinh2xdx
∫sinh2xdx=∫(2ex−e−x)2dx=41(∫e2xdx+∫e−2xdx−∫2dx)=8e2x−e−2x−21x=41sinh2x−21x+C
43. ∫sinh3xdx
∫sinh3xdx=∫sinhxsinh2xdx=∫sinhx(cosh2x−1)dx=∫sinhxcosh2xdx−∫sinhxdx(u=coshx,du=sinhxdx)=∫u2du−coshx=31cosh3x−coshx+C
44. ∫1+x21dx
∫1+x21dx(x=tan(y),dx=sec2ydy)=∫secy1sec2ydy=∫secydy=ln∣secy+tany∣+C(R.T.x=tany,a=1,o=x,h=1+x2)=ln∣1+x2+x∣+C
Alternative
let sinh−1x=y, sinhy=x
=ln∣1+sinh2y+sinhy∣=ln∣1+(2ey−e−y)2+2ey−e−y∣=ln∣4e2y+e−2y−2+4+2ey−e−y∣=ln∣2ey+e−y+2ey−e−y∣=ln∣ey∣=y=sinh−1x
45. ∫ln(x+sqrt(x2+1))dx
∫ln(x+x2+1)dx=∫sinh−1xdx(x=sinhθ,dx=coshθdθ)=∫ln(sinhθ+sinh2θ+1)coshθdθ=∫ln(sinhθ+coshθ)coshθdθ=∫θcoshθdθ=θsinhθ−coshθ+C=xsinh−1x−sinh2θ+1+C=xsinh−1x−x2+1+C
46. ∫tanhxdx
∫tanhxdx=∫coshxsinhxdx,(u=coshx,du=sinhxdx)=∫udu=ln∣u∣+C=ln∣coshx∣+C
47. ∫sechxdx
(sech{x})’ = -sech(x)tanh(x)
∫sechxdx=∫coshx1dx=∫cosh2xcoshxdx=∫sinh2x+1coshxdx(u=sinhx,du=coshxdx)=∫1+u21du=arctanu=tan−1(sinh−1x)+C
48. ∫tanh−1xdx
(y=tanh^-1 x, x=tanh y, dx=sech^2 y dy)
(tanh x)’ = sech^2(x)
∫tanh−1xdx=∫ysech2ydy=ytanh(y)−∫tanh(y)dy=ytanh(y)−ln∣cosh(y)∣=xtanh−1x−ln∣cosh(tanh−1x)∣+C
y=tanh−1xcosh(tanh−1x)=cosh(y)...??
∫tanh−1xdx(tanh−1x→D→1−x21)=(tanh−1x)(x)−∫1−x21xdx=xtanh−1x−∫1−x2xdx(u=1−x2,du=−2xdx)=xtanh−1x+21∫u1du=xtanh−1x+21ln∣1−x2∣+C
49. ∫tanhxdx
∫tanhxdx=∫coshxsinhxdx(u=coshx,du=2coshxsinhxdx)=∫usinhxsinhx2coshxdu=2∫sinhx1du=2∫cosh2x−11du=2∫(u4−1)1/41du
∫tanhxdx=∫coshxsinhxdx(u=coshx,du=sinhxdx)=∫usinhxsinhx1du=∫usinhx1du=∫uu2−11du=∫(u4−u2)1/41du
∫tanhxdx(u=tanh(x),u2=tanhx,x=arctanh(u2))(dx=1−u412udu)=∫u1−u412udu=2∫1−u4u2du=2∫(1−u2)(1+u2)u2du=2∫1−u221+1+u2−21du=∫1−u21−1+u21du=arctanh(u)−arctan(u)=arctanh(tanh(x))−arctan(tanh(x))+C
50. ∫05[x]dx
∫05[x]dxx=[0,1)y=0,x=[1,2)y=1,x=[2,3)y=2...Area=0+1+2+3+4=10
Author: crazyj7@gmail.com